2015
DOI: 10.3906/yer-1404-12
|View full text |Cite
|
Sign up to set email alerts
|

Geodynamic evolution of the Sanandaj-Sirjan Zone, Zagros Orogen, Iran

Abstract: IntroductionThe geology and especially the tectonic style of Iran are highly influenced by the history and evolution of the Tethyan oceans. The Iranian crust is divided into several geotectonic units, namely the Zagros, Makran, Sanandaj-Sirjan Zone, Urmia-Dokhtar Magmatic Assemblage (UDMA), Central Iran block, and Sistan Suture Zone (Figure 1). Each unit is characterized by a relatively unique record of stratigraphy, magmatic activities, metamorphism, orogenic events, tectonics, and overall geological style. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…It is suggested that Middle Permian carbonates of the region were deposited in a shallow marine environment. Correspondingly, similar shallow marine sediments, comprised mainly of subtidal facies were deposited during the middle-late Permian time in the Taurides and Iran (Altıner et al, 2000;Altıner & Özgül, 2001;Altıner & Şahin, 2012;Mehdipour Ghazi & Moazzen, 2015;Rezavand, Jahani, & Asilian, 2016;Şengör, 1990).…”
Section: Paleogeographic Implicationsmentioning
confidence: 95%
“…It is suggested that Middle Permian carbonates of the region were deposited in a shallow marine environment. Correspondingly, similar shallow marine sediments, comprised mainly of subtidal facies were deposited during the middle-late Permian time in the Taurides and Iran (Altıner et al, 2000;Altıner & Özgül, 2001;Altıner & Şahin, 2012;Mehdipour Ghazi & Moazzen, 2015;Rezavand, Jahani, & Asilian, 2016;Şengör, 1990).…”
Section: Paleogeographic Implicationsmentioning
confidence: 95%
“…The SanandajSirjan Zone consists of metamorphic, igneous and sedimentary units of late Neoproterozoic to Neogene age in the hanging wall of the Main Zagros Thrust (Alavi, 1994;Mohajjel et al, 2003;Agard et al, 2005Agard et al, , 2011Mohajjel and Fergusson, 2014;Mehdipour Ghazi and Moazzen, 2015;Shakerardakani et al, 2015;Sheikholeslami, 2015). The Zagros Fold and Thrust Belt has a Phanerozoic succession deformed during the late Eocene to present continental collision between Eurasia and the Arabian continent (Hessami et al, 2001;Alavi, 2004).…”
Section: Zagros Orogen and The Cimmerian Continental Fragmentmentioning
confidence: 99%
“…The Zagros Orogen consists of several parallel NW–SE trending tectonic units, which are from north‐east to south‐west (Figure a): (1) The approximately 150 km‐wide Urumieh–Dokhtar Magmatic belt (UDMB) which formed as a subduction‐related Andean‐type volcano‐plutonic arc during the Eocene to the Quaternary (Alavi, ; Berberian & King, ; Berberian, Muir, Pankhurst, & Berberian, ; Förster, ); (2) The SaSZ (Stöcklin, ) which primarily comprises metamorphic complexes and granitic intrusions representing the internal magmatic and metamorphic portion of the Zagros Orogen (Agard et al, ; Azizi, Zanjefili‐Beiranvand, & Asahara, ; Mehdipour Ghazi & Moazzen, ; Mohajjel & Fergusson, ; Shafaii Moghadam, Khademi, et al, ; Shakerardakani et al, ) and which initiated as a rift zone (Rachidnejad‐Omran et al, ); (3) The Main Zagros Thrust (MZT) or the Main Zagros Reverse Fault (MZRF), which is the suture zone between the Arabian Plate (of Gondwanan affinity) and Eurasia (Agard et al, , ); (4) The High Zagros (or Crush zone) with imbricated tectonic slices comprising Mesozoic limestones, radiolarites, and obducted ophiolite remnants (Agard et al, ); (5) The Zagros Simply Folded Belt characterized by abundant, elongate folds with few surface faults; and (6) The Mesopotamian‐Persian Gulf foreland basin (Alavi, ; Berberian & King, ; Mohajjel & Fergusson, ).…”
Section: Introductionmentioning
confidence: 99%